Extracellular vesicles as potential tools for regenerative therapy - Jose Antonio Rodriguez-Navarro; Jorge Pascual-Guerra; Silvia Sacristan; Maria del Carmen Nogales; Juan Antonio Fafián-Labora; Ana O’Loghlen (Molecular & Cellular Oncology, 2020)
Small extracellular vesicles released by fibroblasts from young human donors diminish lipid peroxidation in senescent cells and in different old mice organs due to their enrichment in Glutathione-S-transferase Mu lipid antioxidant activity.